Criticism of Vocabulary Materials in Arabic Language Learning Books for Foreign Languages - Ritonga, Mahyudin; Ananda, Fitri; Ritonga, Muhammad Jalel; Rosadi, Ahmad (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2023)
The vocabulary aspect is the most important part of learning any language, because the richness of vocabulary will have a good impact on the ability to communicate with the language being learned. In line with that, proportional content of learning resources related to vocabulary is an important thing to pay attention to, therefore, in this article will be presented criticism of Arabic learning resources from the aspect of vocabulary content contained in Arabic textbooks for foreign speakers. The research was conducted by literature review, to facilitate the author in conducting this study, publish or perish and Vosviewer were used. Data sources are books, articles published in various journals. The results of the analysis prove that Arabic textbooks need to be reformulated from the vocabulary aspect, this is because the vocabulary content has not shown proportionality according to each level, the gradation of each level is not strong, the use of vocabulary that is not in accordance with the character of the learner. The limitation of this research is in the aspect of data analyzed in the form of literature data, therefore enthusiasts of Arabic language learning studies can deepen it by conducting empirical studies.